Molecular pathology as a diagnostic aid in difficult-to-classify melanocytic tumours with spitzoid morphology. (May 2021) - Zaremba, Anne; Lodde, Georg; Murali, Rajmohan; Philip, Manuel; Cosgarea, Ioana; Jansen, Philipp; Chorti, Eleftheria; Rose, Christian; Hemmerlein, Bernhard; Matull, Johanna; Thielmann, Carl M.; Kretz, Julia; et al.
Abstract: Accurate classification of melanocytic proliferations has important implications for prognostic prediction, treatment and follow-up. Although most melanocytic proliferations can be accurately classified using clinical and pathological criteria, classification (specifically distinction between nevus and melanoma) can be challenging in a subset of cases, including those with spitzoid morphology. Genetic studies have shown that mutation profiles differ between primary melanoma subtypes and Spitz nevi. These differences may aid in distinguishing benign from malignant in some melanocytic tumours. Here, we present a selection of melanocytic proliferations with equivocal histopathological criteria, wherein genetic analysis was requested to help guide classification. In two of four cases, the genetic results offered valuable insights, allowing a definitive diagnosis, indicating the diagnostic value of mutation profiling in a real-world routine clinical setting. Although histopathological assessment remains decisive in melanocytic proliferation classification, we recommend including genetic profiling in cases of borderline or atypical lesion to support accurate classification. Highlights: Mutation analysis can be a diagnostic aid in determining the dignity in some spitzoid tumours. Where no gene mutations are identified, translocation analysis should be considered. Molecular analysis aids in identifying malignant tumours to be treated as melanoma.